EXAMİNİNG THE FACTORS AFFECTİNG INDİVİDUALS' DECİSİON TO FİNANCİAL EXCLUSİON FOR RELİGİOUS REASONS (Third Sector Social Economic Review, 2022)
This paper investigates the most important factors affecting the fact that individuals do not open a bank account for religious reasons, based on data from approximately 17,600 people from 23 countries. Data are analyzed by Random Forest Algorithm with SHAP values. As a result of the analysis, it has been revealed that (i) for Turkey, the age of the individual, the labour force participation status and income level and (ii) for the Muslim countries, the age of the individual, the number of bank branches in the country and the per capita income of the country, affect the probability of deciding not to open an account (financial exclusion) for religious reasons. It is thought that the findings obtained provide useful information on what can be done to reduce the level of financial exclusion (increase the level of financial drinking) in Muslim countries.The findings obtained in the study provide useful information for both Turkey and the countries where the majority of the population is Muslim to reduce the level of financial exclusion and increase the level of financial inclusion. Namely, countries that want to include their individuals who prefer financial exclusion for religious reasons into the Islamic financial system should try to offer Islamic banking products and services to those over the age of 60 and with a low income level.
Keywords: Financial exclusion; bank account; religion; financial inclusion; random forest